Спекуляція як повсякденне явище в житті мешканців Чернігова у післявоєнне десятиліття (1943-1953 рр.) - Савицька, О. (Сiверянський лiтопис, 2015)
У статті розкрито суть спекуляції як повсякденної практики виживання в умовах
післявоєнної розрухи. Проаналізовано різновиди масових спекуляцій в умовах складної
економічної ситуації та низького життєвого рівня населення. Схарактеризовано
стратегії пристосування до умов життя шляхом використання різних спекулятивних схем, які реалізовувало населення в умовах недостатнього і нерівномірного споживчого забезпечення у період післявоєнної відбудови. В статье раскрыта суть спекуляции как повседневной практики выживания в условиях послевоенной разрухи. Проанализированы разновидности массовых спекуляций
в условиях сложной экономической ситуации и низкого жизненного уровня населения.
Охарактеризованы стратегии приспособления к условиям жизни путем использования различных спекулятивных схем, которые реализовывало населения в условиях недостаточного и неравномерного потребительского обеспечения в военное время на
освобожденных от оккупантов территориях в период послевоенного восстановления. The article reveals the essence of speculation as of practice everyday survival in the
post-war devastation. Particularly marked specificity speculation in war and post-war
reconstruction. The article outlined the most common objects of speculation. Outlines the basic
sectors of the population who resorted to speculative schemes. Analyzed variations massive
speculative schemes in low living standards. Particular attention is paid to the description
of speculation by buying deficient of essential goods and reselling them at inflated prices.
Separately considered types and features speculation committed by officials. Analyzed
speculation and abuse in the case of the issuance and distribution of food and manufactured
cards. Highlights the use of speculation by officials to pay for contract work. Considered the
illegal scheme of artisans and private traders to make a profit. Separately analyzed making
moonshine for sale. Solved speculative schemes during the currency reform in 1947.